PNEUMOCYSTIS PNEUMONIA IN PATIENT INFECTED WITH HUMAN IMMUNODEFICIENCY VIRUS. : JPUMHS;2024:14:04,100-107 .http://doi.org/10.46536/jpumhs/2024/14.04.566 - Abdul Hameed1, Muhammad Bilal2, Imran Khan3, Mian Fareezuddin4, Yaseen Khan5 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: A serious opportunistic lung infection, pneumocystis pneumonia PCP primarily affects people with weakened immune systems, such as those who are HIV positive. Even with improvements in prevention and antiretroviral treatment, PCP still has a major impact on morbidity and death, particularly in environments with limited resources. The aim of study is to determine the frequency of Pneumocystis pneumonia in patients with human immunodeficiency virus HIV presenting to a tertiary care hospital. METHODS: We conducted a cross-sectional study at the Department of Internal Medicine, Lady Reading Hospital, Peshawar, from October 9, 2021, to April 9, 2022. A total of 150 HIV-positive patients, aged 18 to 75 years, took part in the study. To focus on PCP alone, we excluded those with other major health conditions such as tuberculosis, diabetes, kidney or liver disease, or those who were pregnant or using long-term steroids. Each patient underwent a clinical examination and relevant tests to check for PCP. RESULTS: The average age of the participants was 39.92 ± 14.09 years. PCP was diagnosed in 55 patients 36.7%. It was significantly more common in individuals with CD4 counts under 200 cells/mm³ p < 0.001 and in those who had gone longer without HIV treatment p = 0.02, recurrent non-PCP pneumonia p = 0.002, and unexplained fever lasting ≥2 days p < 0.001 were all significantly associated with PCP. There was no statistically significant correlation between genders wise p = 0.45 and also Age groups p = 0.51. CONCLUSION: More than a third of the HIV positive patients in our study had PCP. These results stress the need for early detection and proper care to prevent serious outcomes in vulnerable individuals.